مفهوم النص بين منظور التراث ورؤية الحداثة وأثره في صياغة نظرية النص الأدبي - صدار، نور الدين; بني دومي، خالد قاسم (اتحاد الجامعات العربية - الجمعية العلمية لكليات الآداب, 2021)
يهدف هذا البحث إلى مناقشة إشكالية مفهوم النص بين التراث النقدي العربي والفكر النقدي الغربي، وبيان أثره في صياغة نظرية النص الأدبي المعاصرة؛ وهي الإشكالية التي تنطلق من فرضية مؤداها أن الفكر النقدي العربي قد أصل لمكونات هذه النظرية التي نجد لها جذورا ومرجعيات في تراثنا النقدي والأدبي والبلاغي والفلسفي. ومن ثم فإن نظرية النص في الفكر النقدي المعاصر هي امتداد لهذا الإرث. بالاستفادة من إنجازات الفلاسفة والألسنيين والنقاد، وإنجازات المناهج النقدية المعاصرة. ويأتي البحث للإجابة عن أسئلة مهمة أبرزها: هل كانت الدراسة النقدية معنية بالتنظير للنص؟ وهل يمتلك التراث النقدي آليات للتعامل مع النص؟ وما دور هذا الإرث النقدي التراثي في صياغة نظرية النص الأدبي المعاصرة؟ للإجابة عن هذه الأسئلة، اتبعنا خطة إجرائية تقع في ثلاثة محاور: الأول خصصناه لتحليل مكونات النظرية النصية ومرجعياتها في تراثنا النقدي والبلاغي. الثاني تناولنا فيه مكونات النظرية النصية في الفكر النقدي الغربي. الثالث تناولنا فيه أثر مفهوم النص -كما سيأتي بيانه -في صياغة معالم نظرية النص الأدبي وأبعادها.
This research aims to discuss the problem of the textual concept in the Arab critical heritage and the Western critical thought and to show its impact on formulating the contemporary literary textual theory. It is the problem that stems from the assumption that Arab critical thought has originated in the components of this theory, which we find have roots and references in our critical, literary, rhetorical and philosophical heritage. Hence, the textual theory in the contemporary critical thought is an extension of this legacy, benefiting from the achievements of philosophers, linguists and critics, and the achievements of contemporary critical approaches. The research attempts answer some important questions such as: was the critical study concerned with theorizing the text? Does the critical heritage have the mechanisms for dealing with the text? What is the role of this critical heritage in the formulation of contemporary literary textual theory? To answer these questions, we follow a procedural plan that falls into three axes. The first one is dedicated to the analysis of the components of textual theory and its references in our critical and rhetorical heritage. The second one is devoted to the components of the textual theory in the Western critical thought. The last one is dedicated to the effect of the concept of the text in formulating the features and dimensions of the literary textual theory.
Keywords: النصوص الأدبية -- الدراسات النقدية -- النقد الأدبي -- التراث العربي -- الحداثة